2017
DOI: 10.1186/s12943-017-0659-y
|View full text |Cite
|
Sign up to set email alerts
|

The emerging roles and therapeutic potential of exosomes in epithelial ovarian cancer

Abstract: Ovarian cancer (OC) is one of the three types of malignant tumors in the female reproductive system, and epithelial ovarian cancer (EOC) is its most typical form. Due to the asymptomatic nature of the early stages and resistance to chemotherapy, EOC has both a poor prognosis and a high fatality rate. Current treatments for OC are very limited, and the 5-years survival rate is approximately 30%. Exosomes, which are microvesicles ranging from approximately 30-100 nm in size that are secreted by living cells, can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
81
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 73 publications
0
81
0
Order By: Relevance
“…Combining MTA1dE4 expression and AFP levels would be of great value to further stratify patients for determining optimal treatment and follow‐up. Previous studies have demonstrated that MTA1 is detectable in serum of patients with cancers . If plasma levels of MTA1/MTA1dE4 can also be detected during follow‐up after resection for HCC, it would be very useful for timely prediction of HCC recurrence in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Combining MTA1dE4 expression and AFP levels would be of great value to further stratify patients for determining optimal treatment and follow‐up. Previous studies have demonstrated that MTA1 is detectable in serum of patients with cancers . If plasma levels of MTA1/MTA1dE4 can also be detected during follow‐up after resection for HCC, it would be very useful for timely prediction of HCC recurrence in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, cancer cells secrete more exosomes than healthy cells, and the exosomes cargoes differ. Cancer cell-derived exosomes can provide a suitable microenvironment for cancer cell proliferation, drug resistance, angiogenesis, invasion, immune modulation, and premetastatic niche formation (19). In addition, exosomes are suitable for use as a "liquid biopsy" for malignancies, because they are very stable, easy to obtain, and present in almost all body liquids (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…76,77 MiR-222-3p induces polarization of tumour-associated macrophages by the activation of SOCS3/ STAT3 pathway to facilitate tumourigenesis and cancer progression. 78 Additionally, Rab27a supports exosome could modify the tumour microenvironment via advancing recruitment and differentiation of bone marrow-derived neutrophils to cancer cells. 79 Furthermore, a few studies suggest that tumour-derived EVs facilitate cancer progression by attenuating immune and more specific EVs could diminish the cytotoxicity of natural killer cells and T cell in immunoreaction.…”
Section: Modul Ation Of the Tumour Microenvironmentmentioning
confidence: 99%